Combating hypoxemia in COVID-19 patients with a natural oxygen carrier, HEMO2Life® (M101). (January 2021) - Lupon, Elise; Lellouch, Alexandre G.; Zal, Franck; Cetrulo, Curtis L.; Lantieri, Laurent A.
Abstract: Background: Infection with SARS-CoV-2 is responsible for the COVID-19 crisis affecting the whole world. This virus can provoke acute respiratory distress syndrome (ARDS) leading to overcrowed the intensive care unit (ICU). Over the last months, worldwide experience demonstrated that the ARDS in COVID-19 patients are in many ways "atypical". The mortality rate in ventilated patients is high despite the application of the gold standard treatment (protective ventilation, curare, prone position, inhaled NO). Several studies suggested that the SARS-CoV-2 could interact negatively on red blood cell homeostasis. Furthermore, SarsCov2 creates Reactive Oxygen Species (ROS), which are toxic and generate endothelial dysfunction. Hypothesis/objective(s) We hypothesis that HEMO2Life® administrated intravenously is safe and could help symptomatically the patient condition. It would increase arterial oxygen content despite lung failure and allow better tissue oxygenation control. The use of HEMO2Life® is also interesting due to its anti-oxidative effect preventing cytokine storm induced by the SARS-CoV-2. Evaluation of the hypothesis: Hemarina is based on the properties of the hemoglobin of the Arenicola marina sea-worm (HEMO2Life®). This extracellular hemoglobin has an oxygen capacity 40 times greater than the hemoglobin of vertebrates. Furthermore, the size of this molecule is 250 times smaller than a human red blood cell, allowing it to diffuse in all areas of the microcirculation, without diffusing outside the vascular sector. It possesses an antioxidative property du a Superoxide Dismutase Activity. This technology has been the subject of numerous publications and HEMO2Life® was found to be well-tolerated and did not induce toxicity. It was administered intravenously to hamsters and rats, and showed no acute effect on heart rate and blood pressure and did not cause microvascular vasoconstriction. In preclinical in vivo models (mice, rats, and dogs), HEMO2Life® has enabled better tissue oxygenation, especially in the brain. This molecule has already been used in humans in organ preservation solutions and the patients showed no abnormal clinical signs. Consequences of the hypothesis: The expected benefits of HEMO2Life® for COVID-19 patients are improved survival, avoidance of tracheal intubation, shorter oxygen supplementation, and the possibility of treating a larger number of patients as molecular respirator without to use an invasive machine.